Tectonic plates moment of inertia and angular momentum determination: the case of the Antarctic plate - Savchyn, I.; Tretyak, K. (Ukrainian Antarctic Journal, 2023)
The main goal of this study is to develop and test an algorithm for determining the moment of inertia and angular momentum of a tectonic plate based on the processing of time series of daily solutions of continuous GNSS (Global Navigation Satellite System) stations. The proposed algorithm consists of four consecutive stages: reformatting data to the internal format; dividing the plate into cells and determining their masses; determining the rotation poles and distances from cells to the poles; calculating the plate’s moment of inertia and angular momentum. The algorithm uses freely available time series of daily solutions from continuous GNSS stations or any other data prepared in a similar format. The algorithm is tested for determining the moment of inertia and angular momentum of the Antarctic plate based on the processing of time series of daily solutions of continuous GNSS stations for the period 1995–2021. It is confirmed that the Antarctic Plate’s rotation poles, moment of inertia, and angular momentum are dynamic parameters. However, additional calculations and in-depth comprehensive analysis are required to determine the causes of such dynamics. As a result of comparing, the dynamics of changes in the Antarctic Plate’s rotation poles partially compensate for the unevenness of the Earth’s rotation to keep the angular momentum of the Earth constant.